Geología, ciencias de la tierra, ciencias de la naturaleza: paisaje de un aprendizaje global - Anguita, G. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
Notwithstanding its profound contributions to modern Science, Geology importance in Science Education has been (and still is) continuously dwindling. This situation is universal and has historic roots. At the same time, a reintegration of Geology with other sciences has been taking place, resulting in the Earth Sciences. The Earth Sciences concept is better adapted than Geology to new conceptual advances such as Systems Theory, Catastrophe Theory, or Chaos Physics. Nevertheless, caution is of essence when adapting those physico-mathematical theories to a Science whose methods are not mainly experimental but descriptive and historie. One of the present lines of advance in Earth Science Education is based on courses in which biologists and geologists together analyse Earth and Life systems. Viewing towards a farther horizon, we can find courses on Science integrating Biology, Chemistry, Geology and Physics concepts included in the new school curriculum. Although highly commendable in theory, the scheme is probably deemed to result in no real progress towards integrating Science, since it is not accompanied by deep changes in University curricula.